Application of the differential interferometric technique (DInSAR) to unravel the presentday vertical movement in the Glueckstadt Graben, Germany - Paleari C. M.; Crippa B.; Marotta A. M.; Bayer U. (2008)
The availability of a huge amount detailed geological, geophysical, geodetic and remote sensing data covering the crust in a basin environment suggests their integration at regional scale, in order to analyse the mechanisms of formation and evolution of the basins under changing stress. In particular, the broad range of geological and geophysical information can be combined with the results coming from a "quick-look" DInSAR analysis, to unravel small vertical movements, such as those due to salts movements, and, thus, to better exploit the role that salt mobilization plays in a basin area. In this sense, the Glueckstadt Graben region is a good test site for this kind of analysis, since its tectonics has been strongly controlled by salts growth and movements in different times of its evolution. The Glueckstadt Graben is a major structure of the Central European Basin System. It locates along the transition zone between the Fennoscandian Shield and the NW Germany, where it overprints major structural units of the area and thus it plays a crucial role in the understanding of the dynamic of the area. The DInSAR analysis has been performed by using ENVISAT images, centred at the Hamburger Trough and along the SE-NW direction. The methodology is based on the analysis of the interferogram stack, and the relative velocity is obtained by means of the differential phases adjustment. The analysis shows three major parallel areas, SW-NE directed, showing an alternating pattern of relative uplift, south-eastern of the Hamburger Trough, subsidence, in the centre of the Hamburger Trough, toward the Eastholstein Trough, and uplift, towards the Central Glueckstadt Graben, with respect to the Central Glueckstadt Graben or to the Luebeck areas. This pattern is in agreement with the trend highlighted by geological study.